News coverage summary: Dr. Holmes Rolston III awarded the 2003 Templeton Prize - Milligan, Tom, author; Bohlander, Brad, author; Colorado State University. University Relations Department, publisher (Colorado State University. Libraries, 2003)
Additional newspapers, radio, news coverage summary, Dr. Holmes Rolston, III, Awarded the Templeton Prize. Compiled by University Relations Department, Media and Community Relations. Associated Press, 202 newspapers, circulation 15 million. Gannett News Service, 14 newspapers, circulation 740,000. Religious News Service, newspapers with circulation 870,000. United Kingdom and International Circulation, 1.7 million. NPR All Things Considered, listening audience 12 million.
Keywords: Templeton Prize; Rolston, Holmes, 1932-2025; philosophy professor; Colorado State University